Physical abuse of young children reported by medical professionals in the United States 2014–2023 - Hughes Garza, Holly; Piper, Karen E.; Lawson, Karla A. (Frontiers in Pediatrics, 2026)
BackgroundMedical professionals play an important role in identifying suspected physical abuse of young children, who are at higher risk of serious or fatal abuse, and reporting it to child protection agencies. A recent publication suggested the rate of investigations of physical abuse in infants stemming from medical professionals' reports may be increasing.ObjectivesTo evaluate trends in rates of investigation of physical abuse concerns involving children under 5 years of age reported by medical professionals in the United States from 2014 to 2023, within the context of concurrent changes to national reporting rules, and to examine rates of substantiation of such reports, and resulting rates of entry into foster care.MethodsThe National Child Abuse and Neglect Data System Child Files were used to identify investigated reports for this cohort study. Four states showing abrupt increases in investigations of physical abuse coinciding with changes in national reporting were excluded. Age-specific rates of investigation, substantiation, and foster care entry were calculated, and trend over time was tested using a Mann Kendall trend test. A generalized linear mixed effects model was used to estimate the odds of case substantiation, adjusting for child's age, sex, race/ethnicity, other maltreatment reported, neighborhood conditions, and random effects of state or territory.ResultsOf 285,329 report-child pairs with physical abuse concerns reported by a medical professional, 51% were infants under 1 year of age (n = 146,518). Physical abuse was substantiated in 31% of 284,610 cases with a determination available (n = 86,977), 50% of 237,688 available cases received any type of post-investigation services (n = 119,015), and 18% of 213,986 available cases entered foster care as a result of the investigation (n = 37,698). Population-adjusted investigation rates did not change significantly over the 10 years (p = 0.72). Infants had the highest adjusted odds of substantiation (aOR 2.63, 99% CI 2.57–2.69 vs. children 1–4 years of age). Misclassification of infant prenatal substance exposure as physical abuse presented a significant challenge in assessing trends.ConclusionsThis study suggests rates of investigations of physical abuse concerns involving children under 5 years of age reported by medical professionals in the United States have not significantly increased in recent years.